Enhancing the functional beverage qualities of teter leaf (Solanum erianthum) with various drying temperatures - I GEDE ARIE MAHENDRA PUTRA; PUTU JULYANTIKA NICA DEWI; DEWA AYU ANOM YUARINI; I WAYAN RYANTAMA SWASTIKA BRAJA; I GUSTI AYU KRISMA WIDYA SARASWATI; DINA PUTI KARTIKA (Asian Journal of Agriculture, 2026)
Abstract. Putra IGAM, Dewi PJN, Yuarini DAA, Braja IWRS, Saraswati IGAKW, Kartika DP. 2026. Enhancing the functional beverage qualities of teter leaf (Solanum erianthum) with various drying temperatures. Asian J Agric 10 (1): g100183. https://doi.org/10.13057/asianjagric/g100183. Teter plant (Solanum erianthum) is cultivated and widely available in Taro Village, Bali, Indonesia, and its leaves have been known for their bioactive compounds with health benefits. Traditionally, the leaf is processed by the local community into loloh don teter, a herbal beverage prepared without preservatives with a short shelf life. To enhance stability and functional potential, this study developed teter leaf herbal tea and evaluated the effect of drying temperature on its chemical and sensory characteristics. A Completely Randomized Design (CRD) was used with four drying temperatures (40, 50, 60, and 70°C) for 24 h, with four replications; a total of 16 experimental units. The parameters analyzed included yield, moisture content, antioxidant activity (DPPH), total phenols, tannins, flavonoids, vitamin C, and sensory attributes (color, aroma, taste, and overall acceptance). Data were analyzed using Analysis of Variance (ANOVA) followed by Tukey’s post hoc test (α=0.05). Drying temperature had no substantial effect on yield but significantly influenced moisture content, antioxidant activity, total phenols, tannins, flavonoids, vitamin C, and overall sensory acceptance. Teter leaf dried at 50°C (T2) produced the best quality. It was evident from the stable panelist preference scores in the neutral category for color (3.41), aroma (3.36), taste (3.23), and overall acceptance (3.27). The T2 sample showed the best performance across various parameters, with a primary focus on 19.49% yield, 8.60% moisture content, 85.55% antioxidant activity, total phenols at 40.72 mg GAE/g, tannins at 0.80 mg TAE/g, flavonoids at 28.76 mg QE/g, and vitamin C at 8.13 mg AAE/g. In conclusion, drying at 50°C represents an optimal processing condition that preserves bioactive compounds and maintains acceptable sensory quality, supporting the development of teter leaf herbal tea as a stable functional beverage with high antioxidant potential.